Akuntabilitas Dana Lingkungan Hidup Indonesia: Studi Kasus pada Program Dana Bergulir Sektor Kehutanan - Mais, Rimi Gusliana; Baya, Hindar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study examines accountability mechanisms within the Indonesian Environment Fund (IEF) using a qualitative case study approach. It analyzes institutional practices, financial governance structures, and key challenges in managing environmental funds, with particular emphasis on the revolving fund program for forestry enterprises. The findings indicate that IEF demonstrates strong institutional commitment to accountability through the internalization of “ECO CARES” values, supported by a multi-tiered governance framework that includes the Internal Audit Unit, Supervisory Board, Audit Committee, and oversight from the Directorate General of Treasury, complemented by layered audits and disclosure mechanisms. Despite these strengths, several limitations persist. Fragmented information systems, semi-manual processes, slow digitalization, and persistent non-performing loans hinder transparency, real-time monitoring, and effective fund management. Addressing these issues requires integrated digital systems, enhanced credit risk management, capacity building, and strengthened internal and external oversight, particularly through empowering the Internal Audit Unit (SPI). The study contributes to the discourse on climate finance accountability in the public sector and offers policy insights for strengthening environmental fund governance under the Public Service Agency (PSA) model, with particular relevance for developing countries such as Indonesia.